2003
DOI: 10.1021/ic0342503
|View full text |Cite
|
Sign up to set email alerts
|

Pressure-Induced Enhancements of Luminescence Intensities and Lifetimes Correlated with Emitting-State Distortions for Thiocyanate and Selenocyanate Complexes of Platinum(II) and Palladium(II)

Abstract: The luminescence properties of thiocyanate and selenocyanate platinum(II) and palladium(II) complexes show strong variations with temperature and pressure. The d-d luminescence band maxima for [Pt(SCN)(4)](PPh(4))(2) (1), [Pt(SCN)(4)](n-Bu(4)N)(2) (2), and [Pt(SeCN)(4)](n-Bu(4)N)(2) (4) complexes are centered at ca. 14500 cm(-1) whereas those of the [Pd(SCN)(4)](n-Bu(4)N)(2) (3) and [Pd(SeCN)(4)](n-Bu(4)N)(2) (5) complexes are approximately 2000 cm(-1) lower in energy. Low-temperature luminescence spectra from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
50
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 37 publications
(61 citation statements)
references
References 60 publications
10
50
1
Order By: Relevance
“…Other square-planar complexes with d 8 configured metal centers and +2 oxidation states show similar shifts, such as +24 cm −1 /kbar for (nBu 4 N) 2 Pt(SCN) 4 21 and +29 cm −1 /kbar for (n-Bu 4 N) 2 Pd-(SCN) 4 . 21 Variable-pressure absorption spectra also show similar shifts, such as +13 cm −1 /kbar for Ni[(C 2 H 5 ) 2 P(CH 2 ) 2 P-(C 2 H 5 ) 2 ]I 2 35 and +13 cm −1 /kbar for Ni(isopropyl-PPh 2 ) 2 Br 2 . 35 According to these numerical values, the shift of the luminescence maxima observed for Pt(MeDTC) 2 is quite surprising, being significantly higher with a value of +47 ± 3 cm −1 /kbar.…”
Section: ■ Introductionmentioning
confidence: 79%
“…Other square-planar complexes with d 8 configured metal centers and +2 oxidation states show similar shifts, such as +24 cm −1 /kbar for (nBu 4 N) 2 Pt(SCN) 4 21 and +29 cm −1 /kbar for (n-Bu 4 N) 2 Pd-(SCN) 4 . 21 Variable-pressure absorption spectra also show similar shifts, such as +13 cm −1 /kbar for Ni[(C 2 H 5 ) 2 P(CH 2 ) 2 P-(C 2 H 5 ) 2 ]I 2 35 and +13 cm −1 /kbar for Ni(isopropyl-PPh 2 ) 2 Br 2 . 35 According to these numerical values, the shift of the luminescence maxima observed for Pt(MeDTC) 2 is quite surprising, being significantly higher with a value of +47 ± 3 cm −1 /kbar.…”
Section: ■ Introductionmentioning
confidence: 79%
“…Excitation of 1 a (60 mm in H 2 O) at l = 410 nm gave a weak emission at 563 nm, which is attributed to the 3 MLCT excited state. [7] Complex 1 b has its emission l max at 522 nm, whereas 2 and 3 exhibit a weak emission, with l max at 656 nm in DMSO/H 2 O and 631 nm in H 2 O, respectively. Owing to the extended p-conjugation of the naphthyl group, the 656 nm emission of 2 is assigned to have a 3 IL (intra-A C H T U N G T R E N N U N G ligand) character.…”
Section: H T U N G T R E N N U N G (Thpy)-a C H T U N G T R E N N U Nmentioning
confidence: 98%
“…[7] In previous work, we and others have demonstrated that significant changes in the emission properties of platinum(II) complexes in solutions can be induced by the presence of biomolecules. [4,8,9] Further study on the complex [PtA C…”
mentioning
confidence: 94%
“…A promising direction for future spectroscopic work is the application of external perturbations, such as pressure, which could affect the magnetic order of the title materials and simultaneously greatly enhance the luminescence intensity, as has been shown recently for diamagnetic complexes of palladium(II) and platinum(II) [48,49]. Attractive compounds for future studies include recently described bimetallic complexes with radical ligands [50] and nickel(II) complexes where the imino nitroxide radical ligand shows linkage isomerism [51].…”
Section: Optical Spectra Of D-block Metals With Nitronyl Nitroxide Ramentioning
confidence: 99%